Sodiophilic Interface and Electrolyte Regulation Boost the Lifespan of Anode‐Free Sodium Battery - Huimin Ji; Chunlin Xie; Rui Zhang; Hao Wu; Jiawen Dai; Sihan Li; Qi Zhang; Dan Sun; Yougen Tang; Peiyu Wang; Tian Qiu; Haiyan Wang (SusMat)
ABSTRACT Anode‐free sodium batteries (AFSBs) have attracted increasing attention for their high energy density. However, they suffer from rapid capacity decline resulting from sodium dendrite growth at the sodium/host interface and irreversible side reactions at the electrolyte/sodium interface. Herein, a GaInSn‐coated Cu foil (G‐Cu), prepared by a simple brush coating method, was applied as the sodiophilic current collector to regulate sodium nucleation behavior. In addition, a nonexpendable functional electrolyte additive, hexamethyldisiloxane (HMDSO), was introduced, which could be absorbed on the sodium surface and serve as a protective layer against corrosion side reactions at the electrolyte/sodium interface. It is interesting to note that this additive barely participated in forming the solid electrolyte interphase. The synergetic effects of sodiophilic interface design and electrolyte regulation enable reversible sodium plating and stripping. Ultimately, the AFSB assembled using G‐Cu and HMDSO electrolyte with a highly loaded Na3V2(PO4)3 cathode (≈12.5 mg cm−2) delivers a discharge capacity of 84.5 mAh g−1 after 200 cycles with a high capacity retention of 87.6%, significantly extending its operation lifespan.